Fabaceae Lindl. in a Conservation Unit in the Semi-Arid Region of Paraíba, Brazil - Santos Gomes, Aureliana; de Morais Rodrigues, Erimágna; Coelho Moura, Débora; Miranda De Melo, José Iranildo; de Tasso Moreira Ribeiro, Rayane; de Queiroz, Rubens Teixeira (Phytotaxa, 2022)
The present study consists of a synopsis of Fabaceae in the Pico do Jabre State Park, Paraíba state, northeastern Brazil. 36 species were recorded, subordinate to 24 genera and three subfamilies (Caesalpinioideae, Cercidoideae and Papilionoideae). The genera with the largest number of species were: Senna (six spp.); Mimosa and Chamaecrista (four spp. each) and Centrosema (two spp.). The other genera were represented by one species each. The treatment includes an identification key, information on geographic distribution, flowering and/or fruiting data and images for the species in the area.